Effect of temperature on the development and feeding behavior of Acanthoscelides obtectus (Chrysomelidae: Bruchinae) on dry bean (Phaseolus vulgaris L.). (March 2015) - Soares, Marianne Araújo; Quintela, Eliane Dias; Mascarin, Gabriel Moura; Arthurs, Steven Paul
Abstract: The current study investigated the influence of temperature on the biological and reproductive aspects of the bean bruchid beetle, Acanthoscelides obtectus (Coleoptera: Bruchinae), in common bean ( Phaseolus vulgaris cv. Carioca) under laboratory conditions. To determine thermal constants (fecundity, lifespan and seed consumption), we examined egg-to-adult development under five constant temperatures (16–32 °C). The Briere-1 model best explained the relationship between temperature and developmental rate, providing lower, upper and optimal thresholds of 11.1, 36.1 and 30.3 °C, for both sexes. The thermal constant for total insect development was 687.5 degree-days. Developmental time from egg to adult decreased with increasing temperature >20 °C. Increasing temperature reduced adult lifespan and increased fecundity over the range 24–28 °C. Adult emergence was maximized over the range 20–28 °C, but prolonged at 16 °C and shortened at 32 °C, resulting in fewer emerged adults overall. Beetles consumed less at ≥28 °C, whereas their dry weight was not influenced by the temperature range tested here. These results provide useful knowledge on the biology and thermotolerance of this Brazilian population of A. obtectus in stored beans. Graphical abstract: Highlights: Temperature-dependent development of Acanthoscelides obtectus was described by the nonlinear Briere-1 model. Egg to adult development required 687.5 degree-days. Optimal temperature for development was 30 °C, with thermal thresholds ≤11 °C and ≥36 °C. Optimal temperature for reproduction was 24 °C. Larval consumption and damage to bean seeds were maximized over the range 20–28 °C.